ANALISIS EFEKTIVITAS PROGRAM JEMPOL SEDEKAP KARTU INDONESIA ANAK (KIA): STUDI KASUS KECAMATAN PRAMBON KABUPATEN SIDOARJO - Rizka Amalia; Isnaini Rodiyah (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
This study aims to analyze the effectiveness of the Jempol Sedekap Child Identity Card (KIA) Program in Prambon District, Sidoarjo Regency. A descriptive qualitative approach was used, with data collected through observation, interviews, and documentation. Informants were selected using purposive sampling, including administrative service officers and field implementers of the outreach program. The analysis applied Duncan’s effectiveness theory, which includes goal achievement, integration, and adaptation. The findings show that goal achievement remains suboptimal due to limited implementation frequency and uneven coverage. Adaptation efforts were evident through public consultation forums, but were hindered by a lack of training and limited human resources. Integration with educational institutions such as K3S and IGTKI has been established, but lacks adequate coordination in documentation. The study concludes that the program’s effectiveness needs improvement through better planning, training, and cross-sectoral coordination.